2016
DOI: 10.5296/jsss.v3i2.8922
|View full text |Cite
|
Sign up to set email alerts
|

Corpus-Based Versus Traditional Collocation Learning: The Case of Iranian EFL Learners

Abstract: A vital aspect of word knowledge is knowledge of collocations. Regarding its central role in accurate and fluent use of words, it is essential to consider collocation learning as integral to the study of vocabulary. While different methods are proposed for teaching collocations, the efficiency of these methods is yet subject to question. This study sought to investigate the effectiveness of corpus-based learning of verb-noun collocations as opposed to the traditional methods. To this aim Collin Collocation Dic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Similarly, in Koosha and Jafarpoor (2006) study of traditional and paperbased DDL of propositions, the experimental group outperformed the traditional group in both proposition and collocation learning. Jafarpour et al (2013) and Foomani and Khalaji's (2016) studies showed positive effects of the DDL method on understanding and producing lexical bundles when compared to a traditional approach to teaching collocations using the paper-based DDL approach.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in Koosha and Jafarpoor (2006) study of traditional and paperbased DDL of propositions, the experimental group outperformed the traditional group in both proposition and collocation learning. Jafarpour et al (2013) and Foomani and Khalaji's (2016) studies showed positive effects of the DDL method on understanding and producing lexical bundles when compared to a traditional approach to teaching collocations using the paper-based DDL approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, the number of subjects was so limited that it was fewer than 30 subjects, except for Foomani and Khalaji (2016) study, which had 45 subjects. Additionally, in the Iranian classroom setting, the number of corpora was limited to one corpus, whereas Boulton (2010) found that the number of corpora strongly affects students' ability to learn collocations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is important to note that the proficiency level descriptions in Figure 5 are diverse and may vary depending on the specific framework or context. Some instances include specific levels like advanced [50], pre-intermediate [71,74], upper-intermediate [36,58,65,68], and intermediate [26,52,54,66,69,70], while others have more general descriptions such as beginner-tointermediate [51], intermediate-to-upper-intermediate [72] However, some studies provided no information except the participants' college grades [39][40][41][55][56][57]59,60,[62][63][64]67]. This distribution indicates that corpus-based collocation instruction was investigated across a range of proficiency levels, catering to learners at different stages of language proficiency.…”
Section: Participants' Language Proficiencymentioning
confidence: 99%
“…Jafarpour et al [59] and Koosha and Jafarpour [15] reported the effectiveness of concordancebased methods and DDL in teaching collocations. Men [64] emphasized the positive impact of DDL on collocation production, while Mohammadi and Khalaji [65] found that learners had positive perceptions of corpus-based design. Other studies, such as Yunus…”
Section: Impact Of Corpus-based Instruction On Efl Learners' Collocat...mentioning
confidence: 99%
See 1 more Smart Citation